Analisis Konsentrasi Karbondioksida (CO₂) di Tempat Pemrosesan Akhir Sampah (TPA) Talang Gilo Kota Jambi - Putri Hana Fauzyah; Guntar Marolop Saragih; Hadrah Hadrah (Universitas Batanghari Jambi, 2026)
This study aims to analyze CO₂ concentration levels at TPA Talang Gulo and examine the relationship between CO₂ concentration and environmental factors, including air temperature, humidity, wind speed, and rainfall. The research employed a quantitative descriptive method with field measurements conducted over seven consecutive days at three observation periods each day (morning, afternoon, and evening). CO₂ concentration, air temperature, and humidity were measured using a digital CO₂ meter equipped with temperature and humidity sensors, while wind speed was measured using an anemometer. The collected data were analyzed using descriptive statistics and Pearson correlation analysis to determine the direction and strength of the relationships between variables. The results showed that CO₂ concentrations ranged from 470 to 796 ppm, with higher concentrations generally observed in the morning and lower concentrations in the afternoon and evening. Correlation analysis indicated a strong negative relationship between air temperature and CO₂ concentration, a weak negative relationship between wind speed and CO₂ concentration, and a strong positive relationship between humidity and CO₂ concentration, while rainfall showed a very weak relationship. This study provides quantitative insight into the dynamics of CO₂ concentration in the active landfill zone and serves as a basis for efforts to control greenhouse gas emissions from the municipal solid waste sector in Jambi City.